The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5478/msl.2014.5.4.104
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Methylphenidate, Amphetamine and their Metabolites in Urine using Direct Injection Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Nonmedical use of prescription stimulants such as methylphenidate (MPH) and amphetamine (AP) by normal persons has been increased to improve cognitive functions. Due to high potential for their abuse, reliable analytical methods were required to detect these prescription stimulants in biological samples. A direct injection liquid chromatography-tandem mass spectrometric (LC-MS/MS) method was developed and implemented for simultaneous determination of MPH, AP and their metabolites ritalinic acid (RA) and 4-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A body of work has been done on how to identify the presence of these drugs (25B-NBF, 25C-NBF, and DMBMPP) in the human body for drug detection purposes [37][38][39][40][41] , however little is known about their overall effects and mechanisms of action including potential effects on the microtubule cytoskeleton. As such, there is very limited dosage research for 25B-NBF, 25C-NBF, and DMBMPP.…”
Section: Discussionmentioning
confidence: 99%
“…A body of work has been done on how to identify the presence of these drugs (25B-NBF, 25C-NBF, and DMBMPP) in the human body for drug detection purposes [37][38][39][40][41] , however little is known about their overall effects and mechanisms of action including potential effects on the microtubule cytoskeleton. As such, there is very limited dosage research for 25B-NBF, 25C-NBF, and DMBMPP.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al examined the stability of 25H‐NBOMe, 25B‐NBOMe, 25 E‐NBOMe, 25‐NBOMe, 25C‐NBOH, 25I‐NBOH, 25B‐NBF, 25C‐NBF, and 25I‐N (Seo et al, 2019). They found that all analytes were stable after three freeze/thaw cycles, when stored at room temperature for 1 day, and when stored at 4°C post‐preparation.…”
Section: Stability Of Forensically Relevant Drugs In Biological Matricesmentioning
confidence: 99%
“…The analyte and IS were detected using MRM mode with m/z 56.1, 84.2 and 234.1 for the analyte and 183.1 and 260.2 for the IS, respectively [39]. Other LC-MS/MS methods for quantification of MPH in human plasma [135][136][137], blood, oral fluids [137], hair [138], and urine samples [139,140] are reported in Table 2.…”
Section: Liquid Chromatography (Lc)mentioning
confidence: 99%